Hubungan antara Pengetahuan Budaya Korea dengan Keputusan Pembelian Handphone Korea - Arbaiyah Satriani; Rini Rinawati (MediaTor (Jurnal Komunikasi), 2020)
Indonesian society is currently experiencing a wave of Korean culture (Hallyu) which has also hit various countries. The wave of Korean culture began from a decade ago and has been more intense until now. Korean cultures that are loved by many Indonesian are Korean drama, K-Pop and reality shows that feature Korean artists. Therefore, many business men to take advantage of this situation by utilizing the three types of Korean entertainment to market their products. One of the products is mobile phone namely Samsung and LG. This research seeks information about the relationship between knowledge about Hallyu with Samsung or LG cellphones purchasing decisions that is made by Korean culture fans. This research implements  quantitative method with a total of 40 respondents. The results showed that the knowledge of Korean culture through drama and variety shows "Running Man" contributed substantially to respondents in deciding to buy Korean Samsung and LG mobile phones. On the contrary, knowledge about K-Pop music did not contribute much to respondents in deciding to buy Korean Samsung and LG mobile phones.